WRITTEN LANGUAGE PRODUCTION OF A PERSON WITH LANGUAGE DISORDER : A Case Study of Psycholinguistics on a Student of Bakti Bangsa Junior High School in Sarijadi - Siti Jubaedah, - (2007)
This study entitled, "Written Language Production of a Person with Language Disorder". More specifically, this study tries to discover the language production in written language of a person whose verbal ability is disordered and to figure out the formulated research questions: (1) What does the subject suffer from between Dyslexia and Aphasia, (2) What kind ofwriting aspects such syntactic structure, phonological, and semantic, is mostly problematical. The study uses a student of a Junior high school in Sarijadi. This is a psycholinguistic study that constitutes a cross-field study where it also includes the psychologists, speech therapist, and neurologist to discover the formulated questions. The finding indicates that the person does not suffer from Dyslexia or Aphasia; instead the subject is mentally retarded which some characteristics resemble to that of aphasic and dyslexic in verbal. The most problematic in his writing is on the level of phoneme while the grammatical structure is intact. The subject has difficulty to write double vowel and double consonants* This paper is expected to contribute to those who concern about the issue of psycholinguistics particularly, to the language production of a person with language disorder.